Rural seed sector development through participatory varietal selection: Synergies and trade-offs in seed provision services and market participation among household bean producers in Western Uganda - Wilkus, Erin Lynn; Francesconi, Gian N.; Jager, Matthias (Emerald Publishing Limited, 2017)
Purpose